Implementasi Program Community Development PT. Semen Indonesia (Studi Kasus Pada Masyarakat Desa Sumberarum & Desa Karangloh Kecamatan Kerek, Kabupaten Tuban) - Ilham S.Ant M.PSDM., HC, Rachmad (Fakultas Ekonomi Universitas Gresik, 2020)
This study wants to study the implementation of community development programs by PT Semen Indonesia Tbk in communities in Tuban District especially in the Sumberarum and Karangloh Villages in Kerek District so that later community development programs that are appropriate and sustainable can have a positive impact on surrounding communities, especially in the field of resource development human power. The type of research used is qualitative, data collection instruments used in this study are structured interview guides. The location of this study was carried out in Sumberarum and Karangloh Villages, Kerek District, Tuban Regency to the village community to gather information about community development programs implemented by PT Semen Indonesia. The method used in this study is a qualitative research method. Source of data comes from primary data in the form of interviews and observations. The theory used in this study is the theory of Three Bottom Line, Sustainability Theory, Stakeholder Theory. From the results of the analysis, it is known that various problems that exist in the implementation of CSR activities at PT Semen, in implementing this implementation, the main obstacles in implementing CSR activities are more related to the characteristics and mindset of the community. These included contradictory and pessimistic attitudes built by some of these communities, from the observations of researchers in the field, that attitude was based on the construction of thinking that was wrong about the initial establishment of PT Semen Indonesia factory in the Kerek Subdistrict area. more feasible and prosperous, but in reality not all citizens can be accommodated to work there or in a subsidiary of PT Semen Indonesia.